Ultrasonic material characterization using large-aperture PVDF receivers - Adamowski, J. C.; Buiochi, F.; Higuti, R. T. [UNESP] (Elsevier B.V., 2010)
This work describes the use of a large-aperture PVDF receiver in the measurement of liquid density and composite material elastic constants. The density measurement of several liquids is obtained with accuracy of 0.2% using a conventional NDE emitter transducer and a 70-mm-diameter, 52-mu m P(VDF-TrFE) membrane with gold electrodes. The determination of the elastic constants is based on the phase velocity measurement. Diffraction can lead to errors around 1% in velocity measurement when using alternatively the conventional pair of ultrasonic transducers (1-MHz frequency and 19-mm-diameter) operating in through-transmission mode, separated by a distance of 100 mm. This effect is negligible when using a pair of 10-MHz, 19-mm-diameter transducers. Nevertheless, the dispersion at 10 MHz can result in errors of about 0.5%, when measuring the velocity in composite materials. The use of an 80-mm diameter, 52-mu m-thick PVDF membrane receiver practically eliminates the diffraction effects in phase velocity measurement. The elastic constants of a carbon fiber reinforced polymer were determined and compared with the values obtained by a tensile test. (C) 2009 Elsevier B. V. All rights reserved.
Keywords: Density; Elastic constants; Large-aperture receiver; PVDF; Material characterization